2010
DOI: 10.1093/hmg/ddq083
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in the 3′-UTR of the HDAC6 gene abolishing the post-transcriptional regulation mediated by hsa-miR-433 is linked to a new form of dominant X-linked chondrodysplasia

Abstract: A family with dominant X-linked chondrodysplasia was previously described. The disease locus was ascribed to a 24 Mb interval in Xp11.3-q13.1. We have identified a variant (c.*281A>T) in the 3' untranslated region (UTR) of the HDAC6 gene that totally segregates with the disease. The variant is located in the seed sequence of hsa-miR-433. Our data showed that, in MG63 osteosarcoma cells, hsa-miR-433 (miR433) down-regulated both the expression of endogenous HDAC6 and that of an enhanced green fluorescent protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 34 publications
2
40
0
Order By: Relevance
“…Although less potent than the siRNA, but in agreement with the literature [14,15], miR-98 and Let7a efficiently reduced eGFP expression through c-myc 3 -UTR by destabilizing the mRNA, with limited effects on translation efficiency [35]. Finally, we assessed the capacity of FunREG to reveal post-transcriptional changes from one cell type to another in different pathological contexts (see [19,32]). We first compared cisARS function in cancerous and normal hepatocytes.…”
Section: Validation Of Funreg and Applications In Laboratory Routinesupporting
confidence: 77%
See 1 more Smart Citation
“…Although less potent than the siRNA, but in agreement with the literature [14,15], miR-98 and Let7a efficiently reduced eGFP expression through c-myc 3 -UTR by destabilizing the mRNA, with limited effects on translation efficiency [35]. Finally, we assessed the capacity of FunREG to reveal post-transcriptional changes from one cell type to another in different pathological contexts (see [19,32]). We first compared cisARS function in cancerous and normal hepatocytes.…”
Section: Validation Of Funreg and Applications In Laboratory Routinesupporting
confidence: 77%
“…Genetic changes influencing mRNA decay or translation could also originate from normal events such as polymorphism [1]. In a collaborative work performed with our team, Benoît Arveiler and colleagues recently reported an example of such a genetic defect, which abrogates the regulation of HDAC6 (histone deacetylase 6) expression by miR-433 (see below and [19]). On the other hand, the expression of numerous transRFs (either RBP or miRNA) is altered in diseased tissues [1,10,17].…”
Section: Introductionmentioning
confidence: 99%
“…15 For instance, miR-433 suppresses HDAC6 in human osteosarcoma cells, and a mutation of the miR-433-binding site in HDAC6 mRNA 3'-UTR negates this post-transcriptional regulation in dominant X-linked chondrodysplasia [28]. In addition, it has been reported that in mesenchymal stem cells derived from human adipose tissue, miR-22 promotes osteogenic differentiation and inhibits adipogenic differentiation by suppressing HDAC6 expression [29].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms involved in regulation of HDAC6 expression are poorly characterized, but interestingly, regulation by one specific micro-RNA, hsa-miR-433 is documented. 39 In order to exclude that factors like HIF1 and HSP90 may be involved we analyzed expression levels of both proteins. Especially HSP90 has been reported to regulate functional integrity and turnover of many proteins e.g., the androgen receptor.…”
Section: Discussionmentioning
confidence: 99%